Sensory analysis of cacao liquor (Theobroma cacao L.) in cultivars with different origins grown in the Colombian tropics - Martínez-Guerrero, Nubia Consuelo; Ligarreto-Moreno, Gustavo Adolfo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The sensory profile of 16 cacao cultivars with different origins from the producing areas of the departments of Arauca, Huila and Santander in Colombia was evaluated. This study used the Laboratorio de Calidad Integral de Cacao of the Instituto Nacional de Investigaciones Agropecuarias (INIAP) at the Estación Experimental Tropical Pichilingue (Quevedo-Ecuador), with a panel of four evaluators who analyzed the typical flavor attributes of cacao liquor, such as: cocoa, acid, bitter, astringent, fruity, floral, nutty, sweet and green/raw. The mean values of the scores assigned by the evaluators showed that the sensory profile varied considerably between genotypes and locations. Some genotypes had more complex flavor profiles than the control, CCN 51. The introduced genotypes EET 8, ICS 1, ICS 39 and ICS 60 had a low intensity in the evaluated attributes, while most of the selected regional materials had greater intensity in the fruity, cocoa and nutty notes, especially FLE 3, FSV 41, FEC 2 and FEAR 5. The sensory profiles demonstrated the potential of Colombian cacao with its fine aroma.